INDONESIA-CHILE TRADE COOPERATION: INDONESIA'S INITIAL STEPS TO ENTER THE TPP - Victor Tulus Pangapoi Sidabutar (Manajemen dan Bisnis, 2017)
Trans-Pacific Partnership (TPP) is a trade agreement between the twelve countries in Asia - Pacific region with the aim to encourage the liberalization of trade in member countries, especially in terms of tariffs, trade protection and economy equality. Indonesia indicated its intention to enter the TPP in order to expand the market share of Indonesian exports. Indonesia currently has trade agreements with almost all countries with TPP members, except with Chile, as one of them. The analysis was done by analize Indonesia-Chile's trade in 2011 to 2015; analize Chile's trade with Canada, Singapore and Vietnam and also based on the results of simulations by Petri (2016). The simulation results show that agreement can be beneficial TPP countries involved in it, seen with increasing GDP of member countries. In addition, TPP also increase the flow of inward investment more than outward investment, especially investment coming from countries with high economy. But the free trade agreement (FTA) Indonesia with major trading partners should also be considered before Indonesia joint TPP.